University partnerships for sustainable development - Sengupta, Enakshi; Blessinger, Patrick; Yamin, Taisir Subhi (Emerald Publishing Limited, 2020)
The role of universities is not restricted to merely the exchange of knowledge, they are also responsible for playing a leading role in society. Universities have often come out of isolation to accommodate and facilitate social change, actively engaging in their communities. In order to be socially engaged and effective universities must work closely with industry, non-governmental, and non-profit bodies to identify societal needs and address them productively, working towards achieving common goals and objectives. This volume explores various facets of the Sustainable Development Goals and how well universities have been able to integrate those goals into their curriculum, and institutionalize those goals into their strategic plans and institutional culture. Authors from Nigeria, sub Saharan Africa, Italy and the Middle East have elaborated how to achieve this in the face of shifting expectations, student debt, and graduate mobility.
Includes indexes.
Keywords: College-school cooperation.; Sustainable Development Goals.; Business planning.; Education -- Higher.; Colleges of higher education.; elektronické knihy; electronic books